Predicted oxaloacetate activity, gene expression and viability of human dermal fibroblasts - Nataliya A. Kolotyeva; Larisa V. Limareva; Frida N. Gilmiyarova; Violetta V. Boltovskaya; Pavel V. Ilyasov; Oksana A. Gusyakova; Vasily V. Remizov (Russian Open Medical Journal)
Rationale — The impact of metabolic pathway intermediates on biological processes and cell viability is a topic of fundamental research: functional potential of low-molecular weight biologically active compounds as regulators of metabolic processes, signal molecules, transmitters of intra- and intercellular signals are of special interest; however, this field remains poorly studied. Objective — To perform computer modeling of oxaloacetate biological activity and to evaluate its effect on human dermal fibroblast culture. Material and Methods — We predicted biological activity of oxaloacetate using in silico methods. The obtained data demonstrated that oxaloacetate could influence proliferative properties and cell culture viability of dermal fibroblasts. We studied metabolic parameters and enzymatic activity in supernatant and cell culture lysate. Cell viability was assessed via methyl tetrazolium test (MTT). Results — We established that oxaloacetate had a stimulating effect on human dermal fibroblast culture. Conclusion — Our results demonstrated the stimulating role of oxaloacetate in the form of changes in the level of metabolites and activity of enzymes, such as gamma-glutamyl transpeptidase (p=0.0019) and glycerol-3-phosphate dehydrogenase (p<0.0001). We also established that oxaloacetate increased the percentage of viable cells, compared with the control (p=0.028).